Too big, too small : Why the size of the FOMC does matter - Mroziewicz, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The present article discusses the effectiveness of the decision-making body of the Federal Reserve System (Federal Open Market Committee, or FOMC for short) in the context of management. It focuses on the size of the FOMC as a group larger than the optimum of the group’s effectiveness (depending on the study, the optimum size of the group should be three to eight or five to seven people). The article also discusses the potential negative consequences of too large a group and ways to improve group decisions. The last part of the paper includes an explanation of the decision-making structural composition, and thus partially answers the question of why the FOMC consists of seventeen members, and its decision-making composition of twelve.
Keywords: management; public administration; central banking; Federal Reserve System